Academia Brasileira de Vela : percepção dos alunos egressos - Gonçalves, Jônatas Freitas Moraes (2022)
This dissertation sought to identify the main elements of value perception of the graduates of Academia Brasileira de Vela, including profile definition, performance in the business, level of recommendation for courses and clinics, interest in continuing to study, and what they learned from more significant with the teaching methodology used by the professi instructors of the Brazilian Sailing Confederation. The research aims to contribute to a better understanding and propose continuous improvement actions on the current practices of the Brazilian Sailing Academy. A descriptive research was carried out, with data obtained from closed questionnaires through field research with former students through an online platform in a digital environment. Data analysis indicated the egress profile, their perceptions of quality, priority and importance, as well as future perspectives on professional and academic performance to assist in the National Development Plan for Sailing. Among other conclusions, it can be highlighted that it is important to continue studying the actions and activities of Academia Brasileira de Vela, because despite having obtained high levels of satisfaction from graduates today, it is necessary to constantly work to improve the products and services offered, mainly in the regarding the economic viability of the operation, seeking ways to achieve financial self-sufficiency to maintain its activities